Development and evaluation of the plugin for Figma for Accessibility Documentation for Interfaces - DAI - Oliveira, George Moreno De; Monteiro, Ingrid Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Daily services are adapting to the technological reality and, for these to be disseminated, it is necessary to be accessible to all people, by market demand or compliance with laws in favor of accessibility. As part of the process of meeting users' accessibility needs, documentation is prepared to help the development team, supporting communication between the parties involved. With that in mind, this article describes the development and evaluation of the DAI - Plugin for Accessibility Documentation in Interfaces designed for the Figma prototyping system, as part of the Completion of the Course Work in Digital Design. For this, surveys were carried out to know the documents used for documentation of accessibility in the interface, the main communication problems in the team, and the most used tool for creating prototypes. The opportunity to produce a plugin that represents accessibility requirements for interface elements of web systems in prototypes built in Figma was observed. Thus, designers can design the interface and document the accessibility requirements, and developers can access the tool to identify the attributes, listed from the WCAG, that need intervention to make the page elements accessible. After development, usability and observation tests were performed with designers and developers without much experience in accessible projects and verified the potential of DAI in documenting and communicating accessibility attributes. The development and evaluation of the plugin produced for a tool that contains an active community and with the possibility of free use, such as Figma, can be the basis for the creation of new extensions to solve the daily problems of the teams, in the case of this work, communication of accessibility in the interface.